Photoacoustic Imaging in Inflammatory Orthopedic Diseases: Progress toward Precise Diagnostics and Predictive Regulation - Mengyi Huang; Haoyu Yu; Rongyao Gao; Yuxin Liu; Xuhui Zhou; Limin Fu; Jing Zhou; Luoyuan Li (Advanced Science)
Abstract With the intensification of aging issues, inflammatory orthopedic diseases almost occur in the majority of elderly people, which is becoming increasingly severe. Photoacoustic imaging (PAI) is a non‐invasive visualization technique for a clear diagnosis of the inflammation areas through detecting acoustic signals generated by the laser irradiation. The combination of “light input” and “acoustic output” provides unprecedented scalability as well as high penetration depth and resolution. This new imaging technology can also present more anatomical information and feedback status of inflammatory activity for the orthopedic diseases. Especially in inflammation imaging, this technology can effectively supplement current clinical imaging methods in diagnosis, staging, and monitoring of pathophysiological processes. With the rapid development of these new technologies, the goals of precise diagnosis, predictive regulation, and ultimately personalized treatment strategies are becoming increasingly realistic. Herein, this article introduces various orthopedic inflammations and related imaging technology applications. It covers the types of PA nanoprobes and their research progress in orthopedic inflammation, as well as the potential applications of PAI in various aspects. The review also discusses the recent researches and emerging translational applications of PAI in orthopedic inflammation, as well as the prospects and future development challenges of clinical transformation.